Ome TV Application as Media to Practice Speaking Skill: Students’ Perspective - Anggini, Nurasiah; Maryati Salmiah (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This research aims to explore Generation Z students’ perceptions of using the Ome TV application as a digital platform to improve their English-speaking skills. In the era of technological advancement, Ome TV offers real-time video interactions that provide authentic language practice opportunities with native speakers and global users. Using a qualitative descriptive approach, data were collected through interviews with selected Gen Z participants aged 18–24 who have actively used Ome TV. The findings show that Ome TV offers several advantages, including increased speaking confidence, enhanced vocabulary, improved fluency, and flexibility in time and location, which aligns with the independent and digital-based learning preferences of Generation Z. In addition, the spontaneous nature of conversations encourages learners to apply vocabulary in contextual situations. However, several challenges were also identified, such as unstable internet connections, exposure to inappropriate content, and difficulty understanding different accents. Despite these challenges, most participants viewed the experience positively and considered it a valuable supplement to traditional language learning methods. This study concludes that Ome TV can serve as an effective alternative media to support speaking practice, especially for tech-savvy learners. The results are expected to contribute to the development of more interactive and safe technology-based language learning strategies that meet the expectations of today’s digital generation.